Let a , b , c , d be four integers and A = ( a c b d )
such that A is an invertible matrix and A − 1 also have four integer entries.
Find all possible value(s) of a d − b c and input the product of the possible value(s).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You are using the key fact that d e t ( A B ) = d e t A × d e t B for any square matrices A , B . Thus d e t A × d e t A − 1 = 1 . If both A , A − 1 have integer entries, their determinants are also integers, and hence both determinants are 1 or both are − 1 .
Log in to reply
I don't think he's using that fact. This seems like a different solution!
Log in to reply
Yes he is. The inverse matrix is ( k 4 − k 3 − k 2 k 1 ) and so the determinant of the inverse is k 1 k 4 − k 2 k 3 , so the key identity ( a d − b c ) ( k 1 k 4 − k 2 k 3 ) = 1 is just the property of determinants.
Log in to reply
@Mark Hennings – While that is correct, and one way to arrive at that identity, I don't believe that's how Kelvin arrived at it. Look at the line immediately above 1 = ( a d − b c ) ( k 1 k 4 − k 2 k 3 ) : a d − b c = k 1 ( a d − b c ) k 4 ( a d − b c ) − k 2 ( a d − b c ) k 3 ( a d − b c ) Simply factor out ( a d − b c ) 2 and divide both sides by ( a d − b c ) (which must be nonzero, as A is invertible). This gives the desired identity without using det A × det B = det ( A B ) .
Log in to reply
@Jordan Cahn – Sigh. Without realising it, maybe, this is just a proof of the determinant identity for 2 × 2 matrices.
Yes, after I wrote this long solution I find your solution by my friend...
Problem Loading...
Note Loading...
Set Loading...
Since A − 1 = a d − b c 1 ( d − c − b a )
If all of the entries of A − 1 are integers, then we can let
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ a = k 1 ( a d − b c ) b = k 2 ( a d − b c ) c = k 3 ( a d − b c ) d = k 4 ( a d − b c )
Now we have the relation: a d − b c 1 = k 1 ( a d − b c ) k 4 ( a d − b c ) − k 2 ( a d − b c ) k 3 ( a d − b c ) = ( a d − b c ) ( k 1 k 4 − k 2 k 3 )
This can happen only when a d − b c = ± 1 , since k 1 k 4 − k 2 k 3 is also an integer. Therefore the answer is 1 × ( − 1 ) = − 1 .
Example for a d − b c = 1 : A = ( 3 1 5 2 ) , A − 1 = ( 2 − 1 − 5 3 ) .
Example for a d − b c = − 1 : A = ( 2 1 5 2 ) , A − 1 = ( − 2 1 5 − 2 ) .